The relationship between teacher emotional labor and work/family conflict: The mediating role of teacher-colleague relations - Chen, Yidan; Sun, Siyu; Liu, Xiaomei (Acta psychologica, 2025)
Teaching, as a high-pressure profession, encompasses significant emotional labor that inevitably spills over into teachers' personal lives. It is imperative to acknowledge and address the influence of emotional labor in the workplace on teachers' work/family conflict. Using the conservation of resources theory, this research engaged 690 primary and secondary teachers, employing Teacher Emotional Labor Strategies Scale, Teacher-colleague Relations Scale, and Work/family Scale (work-family conflict, and family-work conflict) to examine how teacher emotional labor influence their work/family conflict and the mediating role of teacher-colleague relations. The results of structural equation modeling showed that (1) surface acting was a significant predictor of work/family conflict, but deep acting and the expression of naturally felt emotion were not. (2) teacher-colleague relations mediated the relationship between surface acting and work/family conflict. These findings highlight the role of teachers' emotional labor strategies and teacher-colleague relations in reducing teachers' work/family conflict and promoting teachers' well-being. Implications for the improvement of teacher regulation ability and school environment are identified.